Sustainability in Numbers by Data Analytics - Ramakrishna, Seeram; Hu, Wayne; Rajan, Jose (Springer Nature, 2023)
For a successful delivery of the United Nations Sustainable Development Goals (UNSDGs) and to track the progress of UNSDGs as well as identify the gaps and the areas requiring more attention, periodic analyses on the “research on sustainability” by various countries and their contribution to the topic are inevitable. This paper tracks the trends in sustainability research including the geographical distribution on sustainability research, their level of multi-disciplinarity and the cross-border collaboration, their distribution of funding with respect to the UNSDGs, and the lifecycle analyses. Cumulative publications and patents on sustainability could be fitted to an exponential function, thereby highlighting the importance of the research on sustainability in the recent past. Besides, this analytics quantifies cross-border collaborations and knowledge integration to solve critical issues as well as traditional and emerging sources to undertake sustainability research. As an important aspect of resource sustainability and circular economy, trends in publication and funding on lifecycle assessment have also been investigated. The analytics present here identify that major sustainability research volume is from the social sciences as well as business and economics sectors, whereas contributions from the engineering disciplines to develop technologies for sustainability practices are relatively lower. Similarly, funding distribution is also not evenly distributed under various SDGs; the larger share of funding has been on energy security and climate change research. Thus, this study identifies many gaps to be filled for the UNSDGs to be successful.